Termite species diversity and conservation in a vegetation-rich region of Northeastern Puducherry, India - G. Kaur; T. Anantharaju; S. Gajalakshm; S. A. Abbasi (Global Journal of Food and Agribusiness Management, 2023)
A systematic survey of termite species in Northeastern Puducherry which is part of peninsular India, was carried out. As there is no pre-existing report on the richness or diversity of termifauna in this region, the present work aims to fill this major knowledge gap. The findings are discussed in the context of the quantitative studies on termifauna carried out across the world, as also in terms of the defining traits of the species identified in the survey vis a vis their possible use in biodegrading ligninous biowaste. The latter aspect is particularly relevant to the controlled use of termites by the process named ‘termigradation’, which denotes termite-based biodegradation of waste.